Technique of Qualifying Elements Consolidation in Criminal Law of SCO Member Countries - KOSTYUK, Mikhail; GOLUBOVSKII, Vladimir; KUNTS, Elena; GOSTKOVA, Dinara (Journal of Advanced Research in Law and Economics, 2018)
The relevance of the paper is explained by the complicated international situation, exacerbation of Russia’s relations with Western countries and growth of cooperation with the Asian ones, especially with member states of the Shanghai Cooperation Organization. It is also associated with greater attention paid to the international and national law doctrines and problems pertaining to the regional aspect of this organization. The objective of the research is revealing and describing the particularities of technique of qualifying elements consolidation in criminal law of the Shanghai Cooperation Organization member countries, as well as wording the theoretical provisions which matter for improvement of the criminal law with regard to ensuring the human and civil security, rights and liberties. The leading research method of the problem is the comparative legal one, which enabled to compare the techniques of qualifying elements consolidation, as well as the structure and system of building the criminal codes in the countries under consideration. The paper traces the influence of the unified Soviet legislation on the laws of the Shanghai Cooperation Organization member countries, except the PRC, which explains the structural similarity of their criminal codes, as well as practices in the qualifying elements consolidation technique. It has been determined that the legislation of almost all countries considered provides for the qualifying elements ‘from mercenary motives’, ‘from molester motives’, ‘for covering up another crime’, ‘for facilitating the commission of another crime’. The experience of the PRC, Kazakhstan and Uzbekistan is seen as positive in recording the clarification of some terms in a chapter, article or section as appropriate at the legislation level.